Avaliação dos efeitos de um produto alimentício natural rico em fibras na prevenção e tratamento do câncer colorretal em modelo pré-clínico - Amaral, Luane Aparecida do (2022)
Colorectal cancer (CRC) ranks third in incidence and second in mortality among all cancers in the world, in both sexes, making it a serious public health problem. Studies have shown that dietary fiber triggers beneficial responses in the body, such as the production of short-chain fatty acids (SCFA) and can prevent and reduce inflammatory processes in the gut. Among the fibers, the fibers of brown flaxseed, chia, green banana flour, oat and quinoa stand out. In addition to fiber, textured soy protein can also help increase SCFA production. Thus, the objective of this study was to formulate a Natural Food Product Rich in Fibers (NFRFP) with brown flaxseed, chia, green banana flour, oats, quinoa and textured soy protein and to evaluate the effects on the prevention and treatment of colorectal cancer in a model preclinical. After the formulation of the NFRFP, chemical analyzes were performed to assess the nutritional content. Seventy-eight male Wistar rats were divided into six experimental groups: negative control (ethylenediamine tetraacetic acid - EDTA), positive control (1,2-dimethylhydrazine DMH - 40 mg/Kg) and four groups fed 10% NFRFP + 1, 2-dimethylhydrazine DMH- 40 mg/Kg: pre-treatment protocol, simultaneous treatment and post-treatment protocol. After 24 hours of administration of EDTA or DMH, blood samples were collected from the animals to perform the comet and micronucleus assays. Before euthanasia, blood was collected for hematological, biochemical and cytokine analyses. After euthanasia, the large intestine of the animals was collected for analysis of aberrant crypts. Parametric distribution data were analyzed using analysis of variance (one-way ANOVA) followed by the Tukey test and non-parametric Kruskal–Wallis test followed by the Dunn test. The significance level adopted was p < 0.05. As a result, NFRFP proved to be a good source of fiber and did not change biometric, biochemical, hematological, inflammatory parameters and did not induce signs of toxicity and genotoxicity/carcinogenicity. PANR if also exhibited a chemopreventive effect, in all protocols, with damage reduction (% RD) of 75% in the comet test. Furthermore, the NFRFP it reduced the incidence of aberrant crypt foci by 49.36% in the post-treatment protocol. Therefore, the results suggest the applicability of NFRFP in the human diet due to the benefits, possibility of production on an industrial scale and easy technological application in different products, since it can be incorporated into foods without altering or causing small changes in the sensory characteristics of the final product.